Peran auditor intern pemerintah, motivasi, dan kinerja pegawai negeri sipil - Setiawan, Doddy; Basuki, Murya Arief (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
This study aims to examine the role of the government internal auditor (APIP) on civil servant performance. Further this study analyze the effect of motivation (intrinsic and extrinsic motivation) as mediating variable between the role of the APIP on civil servant performance. The study is conducted in Kudus Regency, Central Java, Indonesia. This research was conducted through a survey with a random sampling method to all civil servants in the Government of Kudus, Central Java, Indonesia. The sample of this research consists of 272 employees. The statistical analysis using SEM-PLS for hypothesis testing. The results shows that the APIP role has positive influence on employee performance. Further, the study provide evidence that intrinsic motivation mediating the relationship between APIP role and the civil servant performance. However, extrinsic motivation do not mediate the relationship between the role of APIP and civil servants performance. The result shows that the increase of APIP role and intrinsic motivation positively affect civil servant performance.